Maritimisation of Maritime Australia - Muraviev, Alexey (Sea Power Centre Australia, Department of Defence, 2013)
This volume examines the notion of a maritime school of strategic thought for Australia, a debate that emerged in 2012 during the development of the 2013 Defence White Paper. The book is the product of a short research project conducted by the Sea Power Centre – Australia in 2013. A series of five seminars were conducted between Canberra, Perth and Sydney, alongside an accompanying call for papers. The volume includes 23 papers which encompass an eclectic mix of perspectives from defence, academia, industry and other government departments. The book also includes in an Annex the declassified Maritime Strategy for the Australian Defence Force.